OPTIMIZATION OF CULTIVATION CONDITIONS FOR RECOMBINANT INFLUENZA VIRUSES EXPRESSING IMMUNODOMINANT M. BOVIS PROTEINS - Voronina , E.; Abay, Zh.; Nurpeisova , A.; Abdrakhmanova , B.; Jekebekov , K.; Sadikalieva , S.; Bulatov , Ye.; Kozhabergenov , N.; Zakarya , K.; Shorayeva , K. (Eurasian Journal of Applied Biotechnology, 2023)
The use of recombinant viral vectors is one of the promising approaches to the creation of a new generation of vaccines against bovine tuberculosis. For the prevention of tuberculosis in cattle, two reassortant recombinant strains of influenza A virus expressing mycobacterial proteins ESAT-6 and TB-10.4 were constructed based on the method of reverse genetics. As a result of optimization of virus cultivation conditions, the cytopathic effect of the virus was recorded on the Vero cell culture. It has been established that the maximum accumulation of viruses is noted when cultivating in a Vero cell culture using a serum-free DMEM medium at a temperature of (37 ± 0.5) ºС, with access to 5% carbon dioxide. The peak of the biological activity of the recombinant strains for both samples reached at 72 hours of the study and lasted for 96 hours. The biological activity of FLU NS_ESAT 6 was 7.50 ± 0.08 lg TCD50/cm3 , and for FLU NS_TB10.4 was 7,75 ± 0,08 lg TCD50/cm3. The results obtained are the basis for the development of viral biomass for work on the creation of an experimental series of vaccines against bovine tuberculosis.